THE ROLE OF RELATED PARTY TRANSACTION AND EARNING MANAGEMENT IN REDUCING TAX AGGRESSIVENESS - Ellyani, Masna; Hudayati, Ataina (Riset Akuntansi dan Keuangan Indonesia, 2019)
This study aimed to examine the influence of related party transactions (RPT) on tax aggressiveness by using earning management as an intervening variable. This study was performed based on the perception that RPT is a positive practice and it is predicted to decrease tax aggressiveness. Besides aiming to find empirical evidence of positive role of RPT in the field of taxation, this study also aimed to test the positive role of earning management in reducing tax aggressiveness. The population of this study was 47 of manufacturing company registered on the Indonesia Stock Exchange for the period of 2014-2016 having transactions with related party (RPT). The analysis method of this study was structural equation model using Partial Least Square (PLS) software. This findings supported the hypothesis that RPT and earning management negatively affects tax aggressiveness. The results of the study also showed that earning management mediate the relationship between RPT and tax aggressiveness.Keywords: RPT, tax aggressiveness, earning management